Using of atomic-emission spectrometry of the dried blood plasma drops in diagnosis and treatment of brain tumors - Buloichik, Janne I.; Maslova, Galina T.; Korzyuk, Victoria V.; Sergei, Mariya A.; Mavrichev, Anatoli S.; Derzhavets, Liliya A. (Journal of the Belarusian State University. Physics, 2017)
With the use of the multichannel atomic-emission spectrometry method, the samples of blood plasma obtained from the patients with brain tumors have been analyzed. The integral estimation of metabolism of the essential elements is given. It has been found that the content of aluminum, iron, calcium, zink was significantly increased for all patients. Semiquantitative results for the calcium distribution over the surface and within the layers of the dried blood-plasma drops have been obtained. It has been revealed that the surface and in depth distribution of calcium in the samples correlates with severity of the disease. Based on analysis of the system albumin – calcium nitrite or – nitrate, the possibility to estimate changes in the transport functions of albumin depending on toxicity of anions has been demonstrated. The proposed method that enables one to estimate the changes in albuminous centers is an effective and sensitive instrument in diagnostication or in treatment of the brain tumors.